Defining quality outcomes for complex-care patients transitioning across the continuum using a structured panel process. Issue 12 (12th July 2013) - Jeffs, Lianne; Law, Madelyn P; Straus, Sharon; Cardoso, Roberta; Lyons, Renee F; Bell, Chaim
Abstract : Background: No standardised set of quality measures associated with transitioning complex-care patients across the various healthcare settings and home exists. In this context, a structured panel process was used to define quality measures for care transitions involving complex-care patients across healthcare settings. Methods: A modified Delphi consensus technique based on the RAND method was used to develop measures of quality care transitions across the continuum of care. Specific stages included a literature review, individual rating of each measure by each of the panelists (n=11), a face-to-face consensus meeting, and final ranking by the panelists. Results: The literature review produced an initial set of 119 measures. To advance to rounds 1 and 2, an aggregate rating of >75% of the measure was required. This analysis yielded 30/119 measures in round 1 and 11/30 measures in round 2. The final round of scoring yielded the following top five measures: (1) readmission rates within 30 days, (2) primary care visit within 7 days postdischarge for high-risk patients, (3) medication reconciliation completed at admission and prior to discharge, (4) readmission rates within 72 h and (5) time from discharge to homecare nursing visit for high-risk patients. Conclusions: The five measures identified through this research may be useful as indicators of overall care quality related to care transitions involving complex-care patients across different healthcare settings. Further research efforts are called for to explore the applicability and feasibility of using the quality measures to drive quality improvement across the healthcare system.